PENGARUH KOMPRES ALOE VERA TERHADAP NYERI PAYUDARA PADA MASA NIFAS DI KLINIK BPM MARDIAH & BPM KLAHIJAH KOTA LANGSA - EMILDA . (JURNAL PENELITIAN KESEHATAN, 2017)
The objective of this research was to identify The Effect of Aloe Vera Compress on Breast Pain during Postpartum Period experienced by mothers at BPM Mardiah Clinic and BPM Khalizah Clinic, Kota Langsa, 2016.The research design used is Quasi Experimental Design with The Posttest Only Control Group Design. This experimental design requires treatments, outcome measures, and experimental units, but it does not use random placements. The Posttest Only Control Group Design needs two types of groups: "Treatment Group" and "Control Group" in which both groups are used to determine the effect of Aloe Vera on breast pain during the postpartum period. The population studied were mothers at BPM Mardiah Clinic and BPM Khalizah Clinic, Kota Langsa. The research at BPM Mardiah was conducted on 3 June to 21 September 2016, while the research at BPM Khalizah was done on 4 June to 12 September 2016.The result of the parametric prerequisite test of the Aloe Vera compress given to "The Control Group" gave P values greater than α = 0.05 (p 0.05). It shows that the normality assumption on "The Control Group" has been fulfilled. Similarly, the result of the parametric prerequisite test of the Aloe Vera compress given to "The Treatment Group" gave P values greater than α = 0.05 (p 0.05). The result of normality assumption shows that both of these variables have been fulfilled.The Independent T-test showed that the average value of breast pain symptoms during the postpartum period experienced by mothers who were given Aloe Vera compress (The Treatment Group) was lower than the average value of breast pain symptoms during the postpartum period experienced by mothers who were not given Aloe Vera compress (The Control Group). The mean value in "The Control Group" was 4.6 ± 1.86, while the mean value in "The Treatment Group" was 2.8 ± 1.64.Based on the results of this study, researcher concludes that there is a significant effect of Aloe Vera compress on reducing breast pain during the postpartum period experienced by mothers at BPM Mardiah Clinic and BPM Khalizah Clinic, Kota Langsa, 2016, where α = 0,05 (p 0, 05).Keywords : Aloe Vera, Breast Pain.